Electromagnetic-guided versus endoscopic placement of nasoenteral feeding tubes: protocol for a systematic review and meta-analysis. Issue 3 (10th March 2021) - Jin, Zheng; Wei, Yaping; Shen, Guofan; Zhang, Xiaofeng
Abstract : Introduction: Current evidence supporting the utility of electromagnetic (EM)-guided method as the preferred technique for nasoenteral feeding tube placement is limited. We plan to provide a meta-analysis to compare the performance of EM-guided versus endoscopic placement. Methods and analysis: Randomised controlled trials evaluating EM-guided versus endoscopic placement will be searched in MEDLINE, EMBASE and CENTRAL from database inception to 30 September 2020. Data on study design, participant characteristics, intervention details and outcomes will be extracted. Primary outcomes to be assessed are complications. Secondary outcomes include procedure success rate, total procedure time, patient recommendation, length of hospital stay and mortality. Study quality will be assessed using the Cochrane risk of bias tool. Data will be combined with a random effects model. The results will be presented as a risk ratio for dichotomous data and weighted mean difference for continuous data. Publication bias will be visualised using funnel plots. We will quantify the effect of potential effect modifiers by meta-regression if appropriate. The quality of evidence will be evaluated according to the Grading of Recommendations Assessment, Development and Evaluation framework. Ethics and dissemination: This study will not use primary data, and therefore formal ethical approval is not required. The findings will be disseminated through peer-reviewed journals and committee conferences. PROSPERO registration number: CRD42020172427.